Comparative Psycholinguistic Analysis: Phonological Acquisition of Two Celebrity Children in Digital Media - Annisa Salsabilla Yudhista; Ani Rakhmawati (Bahtera: Jurnal Pendidikan Bahasa dan Sastra, 2026)
ABSTRACT   This study aims to analyze and compare the phonological acquisition of two three-year-old celebrity children as presented in digital media content. The research employs a descriptive qualitative approach. The data were obtained from the children’s utterances in YouTube videos uploaded by their celebrity parents through observation and note-taking techniques. The utterances were transcribed and analyzed based on the accuracy, stability, and variation of vowel and consonant production, including phoneme substitution and deletion. The findings indicate that both children have acquired basic Indonesia phonemes, although with different levels of articulatory stability. Issa demonstrates more consistent phoneme production, while Naka exhibits greater variability in pronunciation. Such variations are considered a natural part of early childhood phonological development. Furthermore, digital media exposure and the intensity of verbal interaction from parents as public figures provide rich linguistic input and encourage verbal expression, although they do not always result in stable phoneme articulation. This study emphasizes that children’s phonological acquisition is dynamic and influenced by individual developmental factors as well as the digital communication environment. Keywords: Phonological Acquisition; Early Childhood; Psycholinguistics